'A question of equality and choice': same-sex couples' attitudes towards civil partnership after the introduction of same-sex marriage. Issue 1 (3rd April 2017) - Jowett, Adam; Peel, Elizabeth
ABSTRACT: Since the introduction of same-sex marriage, there have been two parallel institutions (marriage and civil partnership) for the legal recognition of same-sex relationships in England, Wales and Scotland. The current study aimed to examine how those in a civil partnership or a same-sex marriage perceive civil partnership in the context of marriage equality. Eighty-two respondents completed a qualitative online survey, and their responses were analysed thematically. The respondents were divided between those who viewed civil partnership as: 1) a stepping stone to equality, and felt that civil partnerships should be discontinued; 2) a form of legal recognition free from cultural baggage, and argued the Government should make civil partnership available for all; or 3) those who displayed ambivalence and conflicting views. We conclude by discussing how the principle of formal equality underpinned opinions on all sides, and what implications this might have for how we understand discrimination.